The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physreva.84.022708
|View full text |Cite
|
Sign up to set email alerts
|

Trap-depth determination from residual gas collisions

Abstract: We present a method for determining the depth of an atomic or molecular trap of any type. This method relies on a measurement of the trap loss rate induced by collisions with background gas particles. Given a fixed gas composition, the loss rate uniquely determines the trap depth. Because of the "soft" long-range nature of the van der Waals interaction, these collisions transfer kinetic energy to trapped particles across a broad range of energy scales, from room temperature to the microkelvin energy scale. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 67 publications
5
36
0
Order By: Relevance
“…This value is necessarily less than but within an order of magnitude of the total cross section due to the finite trap depth. From previous works on trap loss rates of cold atoms due to collisions with foreign gases [35,36], it is known that the trap loss rate varies quite strongly with trap depth especially near the energy scale for quantum diffractive collisions, ϵ d ¼ 4πℏ 2 =mσ T , where m is the mass of trapped particles and σ T is the total collision cross section [37]. This energy scale is on the order of ∼100 mK for the present case.…”
Section: Prl 118 093201 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 71%
See 1 more Smart Citation
“…This value is necessarily less than but within an order of magnitude of the total cross section due to the finite trap depth. From previous works on trap loss rates of cold atoms due to collisions with foreign gases [35,36], it is known that the trap loss rate varies quite strongly with trap depth especially near the energy scale for quantum diffractive collisions, ϵ d ¼ 4πℏ 2 =mσ T , where m is the mass of trapped particles and σ T is the total collision cross section [37]. This energy scale is on the order of ∼100 mK for the present case.…”
Section: Prl 118 093201 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 71%
“…Under such conditions, the number of trapped radicals, N CH 3 , may obey a first order differential equation dN CH 3 =dt ¼ −ð1=τÞN CH 3 , where the lifetime, τ, is inversely proportional to the average of the product of the cross section, σ, velocity, v, and the density, n, of background gas particles [35]. The measurement of background gases by a residual gas analyzer revealed that the major component of the background gas in our vacuum chamber was H 2 (or H) with some N 2 as a minor component (less than 1=3 of H 2 ).…”
Section: Prl 118 093201 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…The steady state number of atoms in the MOT is In the regime where β n ss is small compared to the losses due to background vapor, Γ≃ (a few s −1 to 0.01 s −1 ), Eq. (10) can be approximated by [33] Nt N ss 1 − e −γt .…”
Section: Methodsmentioning
confidence: 99%
“…For rubidium atoms in a magnetic trap, the trap depth can readily be estimated based on the magnetic field gradient, the magnetic properties of the trapped species, and the geometry of the vacuum cell [33]. That is, atoms in a magnetic trap with sufficient energy to reach the wall of the vacuum container will be heated via contact with the wall and escape the trap.…”
Section: Evaluating the Relationship Between V C And V Ementioning
confidence: 99%
See 1 more Smart Citation